Oxazolone and ethanol induce colitis in non‐obese diabetic‐severe combined immunodeficiency interleukin‐2Rγnull mice engrafted with human peripheral blood mononuclear cells. (10th April 2013) - Nolte, T.; Zadeh‐Khorasani, M.; Safarov, O.; Rueff, F.; Gülberg, V.; Herbach, N.; Wollenberg, A.; Mueller, T.; Siebeck, M.; Wolf, E.; Gropp, R.
Summary Oxazolone‐induced colitis in mice has become a recognized model to study the efficacy of therapeutics targeting the immunological response underlying the development of inflammatory bowel disease. However, this model cannot be used when therapeutics designed to address human targets do not interact with the respective murine counterpart. In this study, we examined the induction of oxazolone mediated colitis in non‐obese diabetic‐severe combined immunodeficiency interleukin‐2Rγnull (NOD‐SCID IL2Rγnull) mice engrafted with human peripheral blood mononuclear cells (hPBMC) derived from patients suffering from ulcerative colitis (UC), atopic dermatitis (AD) and healthy volunteers. NOD‐SCID IL2Rγ null mice were engrafted with hPBMC followed by challenge with oxazolone or ethanol vehicle. Mice developed the same symptoms as observed previously in immunocompetent mice. The clinical activity score increased and the colon architecture was characterized by the development of oedema, fibrosis, crypt loss and dense infiltration of predominantly T cells into the lamina propria. Fluorescence activated cell sorter (FACS) analysis of lymphocytes in the colon identified natural killer (NK) T cells as a major constituent. In contrast to studies with immunocompetent mice, we observed the same phenotype in the group challenged with ethanol vehicle. The phenotype was most pronounced in mice engrafted with PBMC derived from a patient suffering from UC, suggesting that the immunological history of the donors predisposes the engrafted mice to react to ethanol. The model described here has the potential to study the efficacy of therapeutics targeting human lymphocytes in a model which is more reflective of the human disease. In addition, it might be developed to elucidate molecular mechanisms underlying the disease.